Community Service "Let's Brush Your Teeth" Innovation Video and Toothbrushing Demonstration as an Effort to Improve Knowledge and Skills Brushing Teeth at MTs Matholibul Ulum, Lebak Village, Pakis Aji District, Jepara Regency, Central Java Province - Febrita Mahsalisa; Imelia Crisanthe; Moch Raja Haffidz; Kelvin Rafi Fahreza; Anggita (Wealth Community Empowerment, 2026)
Dental and oral health is very important, especially for children age school, but often overlooked. Through education engaging health information, such as videos and demonstrations directly, expected student can more understand method brushing correct teeth as well as importance cleanliness mouth. Activities practice managerial Applied Masters Program Students Dental and Oral Therapist Polytechnic of  Health The Ministry of Health of Semarang in 2025 took place at the Pakis Aji Health Center, located on Jl. Raya Jepara Lebak KM 12, Pakis Aji District, Semarang Regency Jepara. Implementation method activity this in the form of devotion community at MTs. Mtaholibul Ulum Village of Lebak region work Pakis Aji Community Health Center. Learning media trensa play a role important in the area of “Gen Z” (Generation Z) refers to the group demographics born mid 1990s to early 2010s. Generation this known with use extensive digital technology and social media. With approach learning video based “ Let’s Brush Your Teeth” and demonstration brushing tooth expected capable increase knowledge and skill about method brushing correct teeth in students grade 1 at MTs. Matholibul Ulum Lebak.